Credit rating initiation and accounting quality for emerging-market firms - Bae, Kee-Hong; Purda, Lynnette; Welker, Michael; Zhong, Ligang (Journal of International Business Studies, 2013)
We examine whether certification by an internationally recognized information intermediary helps emerging-market firms overcome the liability of foreignness in capital markets. Specifically, we ask whether securing a credit rating from Standard & Poor's (S&P) enables these firms to certify their financial reporting quality. We hypothesize that the unique information demands of lenders motivate firms to provide more conservative financial statements upon securing an S&P rating. We find evidence consistent with this conjecture. Moreover, the rating appears to be part of an international expansion strategy for these firms, and is followed by increased international activity in capital and product markets.